Challenges to gaining informed consent in a low-income urban community in Ghana: a case study of Tetegu, Weija Gbawe - Darrold Cordes; Paul Sefah; Dora Marinova (Discover Sustainability)
Abstract There is a lack of data describing the physical, social, economic, and environmental conditions of low-income communities in Sub-Saharan African cities. Research to obtain this data requires informed consent from business owners and heads of households. This case study focuses on a small enclave of approximately 150 households and associated businesses and community services in Tetegu, Accra, Ghana. Low-altitude aerial and terrestrial surveys were conducted to identify all structures, business types, and occupancy levels of households. A sample of businesses and households were purposively chosen as potential participants in the study. Interviews were conducted and informed consent procedures were followed in accordance with the ethics approval. Data was collected online using a computer tablet and informed consent was recorded electronically. Language and literacy barriers required considerable patience when presenting the scope of the research and participants’ roles and rights. Distrust of researchers, resentment, indifference, and aggressive behavior towards researchers were encountered. Other challenges included health and safety concerns and the quality of telecommunication services. Informed consent was obtained from more than 30% of households and 10% of businesses. The research outcomes may not represent other urban low-income communities in Accra or other cities in Ghana, West Africa, or Sub-Saharan Africa.